TINJAUAN ANALIS ATAS PENGATURAN WILAYAH LANDAS KONTINEN DENGAN BERLAKUNYA KONVENSI HUKUM LAUT PBB 1982 - Munsharif Abdul Chalim (Jurnal Pembaharuan Hukum, 2016)
Before the entry into force of UNCLOS 1982, the continental shelf area governed by Article 1 of the Convention IV Geneva Convention on Law of the Sea 1958, which was implemented by Law No. 1 of 1973. The setting through 1958 Geneva Convention on Law of the Sea benefit for the developed countries only that have the advance technology. To be able to realize the regulating of the use of the continental shelf that is equitable, it is necessary to rebuild or reconstruct the form of national law Act No. 1 In 1973 and international law in the form of the Geneva Convention on Law of the Sea 1958. Two things to note in this reconstruction is the reconstruction of value and the reconstruction of law or settings. Although UNCLOS 1982 has been in force, but the status of Indonesian Act No. 1 of 1973 still impose as the implementation of the Geneva Conventions Year 1958. Several agreements with neighboring countries are being held between the years 1969-19972, of course it is very detrimental to the Indonesia Government. Through reconstruction of national law, in this case the Law No. 1 of 1973, adjusted to international law, namely UNCLOS 1982 is expected that the  regulating of the utilization of natural resources in the continental shelf of Republic Indonesia can provide a fair arrangement. It is necessary to remember that there is a difference in perception between the Law No. 1 of 1973 with the UNCLOS 1982 in the matter of setting the area of the continental shelf.